2021
DOI: 10.1186/s13578-021-00649-7
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 alleviates cardiac hypertrophy via regulating Myh7 mRNA decoy

Abstract: Background Pathological cardiac hypertrophy is a major contributor of heart failure (HF), which seriously threatens human’s health world widely. Deregulation of m6A RNA methylation, and m6A methyltransferases and de-methyltransferases have been demonstrated to act essential roles in cardiac hypertrophy and HF. Here, we studied the potential roles and its underlying mechanisms of m6A Reader YTHDF proteins in HF. In this study, we constructed HF mouse model by transverse aortic constriction surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…However, the mechanism by which METTL14 exerts its inhibitory effects remains unknown. At present, a large number of studies have shown that m 6 A modifications caused by the abnormal expression of m 6 A core modification and reading proteins are involved in various physiological and pathological processes, such as biological growth and development, sperm development and maturation, DNA damage repair, biological rhythms, and various types of tumors [ 33 , 46 ]. Chai et al showed that YTHDF2 could promote the malignant progression of gliomas by accelerating UBX domain protein 1 (UBXN1) mRNA degradation via METTL3-mediated m 6 A modification [ 1 ]; Pan et al verified that YTHDF2 could lead to the reduction of Tet1 mRNA decay by binding to m 6 A in Tet1 mRNA [ 47 ]; Hou et al confirmed that the small ubiquitin-related modifier (SUMO)ylation of YTHDF2 could significantly increase the binding affinity of m 6 A-modified mRNAs and subsequently result in deregulated gene expression responsible for cancer progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which METTL14 exerts its inhibitory effects remains unknown. At present, a large number of studies have shown that m 6 A modifications caused by the abnormal expression of m 6 A core modification and reading proteins are involved in various physiological and pathological processes, such as biological growth and development, sperm development and maturation, DNA damage repair, biological rhythms, and various types of tumors [ 33 , 46 ]. Chai et al showed that YTHDF2 could promote the malignant progression of gliomas by accelerating UBX domain protein 1 (UBXN1) mRNA degradation via METTL3-mediated m 6 A modification [ 1 ]; Pan et al verified that YTHDF2 could lead to the reduction of Tet1 mRNA decay by binding to m 6 A in Tet1 mRNA [ 47 ]; Hou et al confirmed that the small ubiquitin-related modifier (SUMO)ylation of YTHDF2 could significantly increase the binding affinity of m 6 A-modified mRNAs and subsequently result in deregulated gene expression responsible for cancer progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…As another member of the IGF2BP family, IGF2BP3 reportedly promotes eIF4E‐mediated translational activation by decreasing the stability of EIF4E‐BP2 mRNA, which in turn enhances the proliferation of tumour cells. 52 In addition, YTHDF2, a common RNA binding protein, has been reported to inhibit the mRNA stability of several target genes, including MYH7, 53 EGFR, 54 UBXN1, 55 LXRA and HIVEP2. 56 As a famous m6A reader, IGF2BP2 can enhance mRNA stability through its recognition of RNA N6‐methyladenosine.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above report, T. Y. Liu et al (2017) generated hnRNP A1 knockout mice, which showing severe muscle development defects, thus resulting in embryonic lethality. Recently, Xu et al (2021) reported the functional importance of YTHD2 in regulating m 6 A methylation during cardiac hypertrophy. First, an increased level of YTHD2 was detected in tissues of mice with cardiac hypertrophy and the protective role of YTHD2 was suggested by less fibrosis, lower ratio of heart weight to body weight, and fewer enlarged cardiomyocytes after TAC‐induced cardiac hypertrophy in mice model that delivering with AAV‐YTHDF2.…”
Section: “Readers” In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…First, an increased level of YTHD2 was detected in tissues of mice with cardiac hypertrophy and the protective role of YTHD2 was suggested by less fibrosis, lower ratio of heart weight to body weight, and fewer enlarged cardiomyocytes after TAC‐induced cardiac hypertrophy in mice model that delivering with AAV‐YTHDF2. The further investigation reported that YTHDF2 interacting with Myh7 mRNA via recognizing its m 6 A site promoted its degradation, thus alleviating myocardial hypertrophy (Xu et al, 2021).…”
Section: “Readers” In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%